Religious Pluralism: Between Syncretism and Tantularism - Moh. Toriqul Chaer (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
This article has several objectives: first, to discover the background of religious pluralism in Javanese society, notably among the communities in Ketanggi; second, to recognize religious practice in Ketanggi; and third, to explore the religious attitudes of Ketanggi people towards religious pluralism. This article is based on field research carried out in Ketanggi sub-district of Ngawi, East Java, which is inhabited by the communities with different religious backgrounds. This paper argues that religious commitment among Ketanggi people is partly based on ‘tantularism’, a sort of ethical principle which emerges as a result of the encounters between religion and local wisdom. The reception of Ketanggi people towards religious and cultural pluralism is expressed through the concept of lilo legowo (voluntary reception towards the other) which in turn becomes foundation of religious tolerance in that area.